O uso da literatura fantástica no ensino de filosofia: considerações a partir de C. S. Lewis - Oliveira, Samuel Sóstenes Silva (2024)
Are philosophy and fantasy literature antagonistic? Despite being a paradoxical relationship, it is possible to perceive the intertwining between both in all aspects, so much so that to disregard one of them is to lose one side of the coin. Through the writings of C. S. Lewis (1898-1963), especially from his elaborate fantasy literature, present in his works, one can see how rich is the use of literature for philosophy, especially for philosophical reflection and didactics. Seeking to establish the possibility and influence of fantasy literature in the teaching of philosophy, the present research focuses on the works of C. S. Lewis, particularly those of a literary nature, whose framework serves as a reference for a dynamic communication of dense concepts of the philosophical context. Although Lewis's works are the focus of its research, this dissertation will be circumcised and referenced by several researchers, educators and critics of Lewis's literature, with the aim of obtaining an adequate understanding of the thought and pedagogical proposals of the British writer as a possibility to soften the rigidity of philosophy teaching for young people, as well as to enable access to it for children who, at the height of their imaginative and creative faculties, will be able to delight in the mythical and fantastic narratives that convey the thought and reflective process of philosophy. In this way, it will be possible to carry out an assessment of how many possibilities can be found in an innovative, but at the same time classical, approach to philosophical praxis. Once it is proven that this method, based on fantasy literature, proves to be productive and efficient, it needs to be incorporated, not only into the philosophy curriculum, as something to be added, but mainly into the method of achieving the effectiveness of teaching, through reflection and dialogue, all the themes common to the teaching of philosophy. This work ends by leaving, as an educational product, a proposal for an elective philosophy course to be used in high school, based on the fantasy literature of C. S. Lewis, especially his literary masterpiece, The Lion, the Witch and the Wardrobe.